2016
DOI: 10.1007/s10995-016-2027-8
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Social Status and Psychological Distress in Mothers of Young Children

Abstract: Introduction Perceptions of social standing have increasingly well-documented relationships with health. Higher subjective social status (SSS) is associated with better psychological well-being among women, and mothers of newborns. The relationship between SSS and psychological distress among mothers of young children, however, is largely unknown. SSS may provide insight into aspects of maternal functioning that are relevant to parenting capacity, as well as insight into future health; in addition, SSS is brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…In terms of demographic characteristics, there was some indication that Black American participants yielded a larger r-value (r=-0.36) than other ethnic groups (e.g., Latinos, mean r=-0.14), while male samples had larger average r-values (mean r=-0.31) than female samples (mean r=-0.15), although the only non-significant correlations were in samples of females. Additionally, all three studies using regression analysis found a significant association between a measure of SSS and depressive symptoms; including in a low income sample (Hamad et al, 2008), and two female only samples (Lau et al, 2013 ;Michelson et al, 2016). Although, when analysing by ethnicity, Michelson et al (2016) found a significant association for just Black women on the SSS-community scale, suggesting that social status within the community may be pertinent for this group.…”
Section: Self-harm and Scs Univarite Findingsmentioning
confidence: 92%
See 3 more Smart Citations
“…In terms of demographic characteristics, there was some indication that Black American participants yielded a larger r-value (r=-0.36) than other ethnic groups (e.g., Latinos, mean r=-0.14), while male samples had larger average r-values (mean r=-0.31) than female samples (mean r=-0.15), although the only non-significant correlations were in samples of females. Additionally, all three studies using regression analysis found a significant association between a measure of SSS and depressive symptoms; including in a low income sample (Hamad et al, 2008), and two female only samples (Lau et al, 2013 ;Michelson et al, 2016). Although, when analysing by ethnicity, Michelson et al (2016) found a significant association for just Black women on the SSS-community scale, suggesting that social status within the community may be pertinent for this group.…”
Section: Self-harm and Scs Univarite Findingsmentioning
confidence: 92%
“…Additionally, all three studies using regression analysis found a significant association between a measure of SSS and depressive symptoms; including in a low income sample (Hamad et al, 2008), and two female only samples (Lau et al, 2013 ;Michelson et al, 2016). Although, when analysing by ethnicity, Michelson et al (2016) found a significant association for just Black women on the SSS-community scale, suggesting that social status within the community may be pertinent for this group. Perceiving oneself to be higher on the SSS ladder was consistently associated with lower prevalence of depressive symptoms (e.g., Adler et al, 2008), with the relationship replicated across different samples (e.g., older adult, pregnant women), SSS contexts (majority used SSS-society scale) and even an experimental manipulation inducing lower SSS increased prevalence of depressive cognitions (Schubert et al, 2016).…”
Section: Self-harm and Scs Univarite Findingsmentioning
confidence: 92%
See 2 more Smart Citations
“…Social support has been shown to play a critical role in positive parenting practices (Andresen & Telleen, ), in early childhood health and development (Kendrick et al., ; Maas, Vreeswijk, & van Bakel, ; Poobalan et al., ), in health (Cohen, Gottlieb, & Underwood, ; Holt‐Lunstad, Smith, & Layton, ), and as a buffer to the psychological impact of stress (Michelson, Riis, & Johnson, ). Social support acts as a mechanism through which “coping, esteem, belonging and competence” (Gottleib, , p 198) are fostered in individuals.…”
Section: Introductionmentioning
confidence: 99%